Characterization and evaluation of morphological features for aggregate in asphalt mixture: A review. (1st March 2021) - Gong, Fangyuan; Liu, Yu; You, Zhanping; Zhou, Xiaodong
Highlights: Review the conventional testing and imaging methods of aggregate morphologies. Collect and discuss the typical methods and evaluation parameters of aggregates. Evaluate and compare different imaging techniques of aggregate morphologies. Provide recommendations to improve characterization and evaluation of morphologies. Abstract: The objective of this paper is to review the current characterization and evaluation methods and introduce emerging technologies of aggregate morphologies in asphalt mixture through conventional tests and imaging techniques that would be possibly applied to analyze and evaluate the morphological features of particles. The current evaluating-characterizing method is defined as a procedure that has been shown by experience or research to obtain satisfying results, that is established or proposed as a standard suitable for general application. This review first identified the methods based on laboratory tests to characterize and evaluate the morphologies of the aggregate particle. Then, an attempt was made to study the existing methodologies from different points of view, accompanied by extensive comparisons on three categories of imaging techniques-early imaging techniques, dynamic imaging techniques, and static imaging techniques to facilitate further research studies. Additionally, the evaluation parameters of aggregate morphologies based on image technologies were represented. Finally, a comparative evaluation between different conventional testing methods and different imaging techniques through basic tools, application conditions, advantages, and disadvantages were conducted. This review concluded with some recommendations and conclusions in terms of morphological characterization and evaluation of aggregates in the asphalt mixture to materials selection during the mixture design and construction.